Cross-monomer substrate contacts reposition the Hsp90 N-terminal domain and prime the chaperone activity - Street, Timothy O.; Lee, Chung-Tien; Mayer, Matthias P. (Journal of molecular biology, 2012)
The ubiquitous molecular chaperone Hsp90 plays a critical role in substrate protein folding and maintenance, but the functional mechanism has been difficult to elucidate. In previous work, a model Hsp90 substrate revealed an activation process in which substrate binding accelerates a large open/closed conformational change required for ATP hydrolysis by Hsp90. While this could serve as an elegant mechanism for conserving ATP usage for productive interactions on the substrate, the structural origin of substrate-catalyzed Hsp90 conformational changes is unknown. Here, we find that substrate binding affects an intrinsically unfavorable rotation of the Hsp90 N-terminal domain (NTD) relative to the middle domain (MD) that is required for closure. We identify an MD substrate binding region on the interior cleft of the Hsp90 dimer and show that a secondary set of substrate contacts drives an NTD orientation change on the opposite monomer. These results suggest an Hsp90 activation mechanism in which cross-monomer contacts mediated by a partially structured substrate prime the chaperone for its functional activity.